Bacterial infection of epithelial signaling - Prince, Alice (Henry Stewart Talks, 2009)
Inhaled bacteria activate Ca2+ fluxes in airway cells, Signal proinflammatory chemokine and cytokine production, Ca2+ acts as a second messenger to stimulate adjacent cells, Ca2+ activates proteases to facilitate PMN transmigration
Archived at 2021/02/25